2003
DOI: 10.1029/2002ja009668
|View full text |Cite
|
Sign up to set email alerts
|

Formation of magnetospheric plasma population regimes coupled with the dynamo process in the convection system

Abstract: [1] Based on the magnetosphere-ionosphere (M-I) coupling scheme, convection as a compound system is considered including the generation of plasma population regimes in the magnetosphere. In these considerations, primary elements that must be set to a selfconsistent configuration are convection flows in the magnetosphere and the ionosphere, field-aligned current (FAC) systems, ionospheric currents, energy conversion processes, and plasma population regimes. The convection in the M-I coupling system is inextrica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
43
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(47 citation statements)
references
References 53 publications
(122 reference statements)
4
43
0
Order By: Relevance
“…The advantage of the MHD approach is that with a help of numerical schemes it realizes self-consistent reproduction of convection through the Bv approach. Many new findings were made by this method as will be seen in the following part of this paper (Tanaka 1995(Tanaka , 1999(Tanaka , 2000a(Tanaka , 2000b(Tanaka , 2001(Tanaka , 2003bFujita et al 2003aFujita et al , 2003b.…”
Section: Magnetosphere-ionosphere Coupling Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The advantage of the MHD approach is that with a help of numerical schemes it realizes self-consistent reproduction of convection through the Bv approach. Many new findings were made by this method as will be seen in the following part of this paper (Tanaka 1995(Tanaka , 1999(Tanaka , 2000a(Tanaka , 2000b(Tanaka , 2001(Tanaka , 2003bFujita et al 2003aFujita et al , 2003b.…”
Section: Magnetosphere-ionosphere Coupling Modelsmentioning
confidence: 99%
“…Since it does not strictly consider the low-beta area in the ionosphere, it does not confront a strict requirement to fully relate the convection with FAC closure processes in the magnetosphere which are coupled to dynamo and plasma distribution in the magnetosphere. As a consequence, it took an unexpectedly long time before we understood how these currents fit in the overall picture, although people had been aware that FACs play a major role in the magnetosphere dynamics (Iijima 2000;Tanaka 2000aTanaka , 2003b. A crucial barrier for these considerations has been the difficulty of considering the magnetospheric closure process of FACs.…”
Section: Discovery Of the Facmentioning
confidence: 99%
See 2 more Smart Citations
“…The reconnected flux tubes formed by transient reconnection then move tailward and poleward under a combination of magnetic tension forces (j×B) and magnetosheath flow. By the time they reach the downstream side of the cusp, the j×B force has reversed and the reconnected flux tubes are extracting energy from the flow (Tanaka, 2003). At the time when flux erosion events were first seen in HEOS 2 data, at a locale comparable to ours, Haerendel et al (1978) suggested that "entry of magnetosheath plasma should not be restricted to the cusp region but may continue further down the tail or along the early morning or late evening flanks, depending on the initial orientation of the external field.…”
Section: The Observations In the Context Of Solar Windmagnetosphere Imentioning
confidence: 99%